PELATIHAN BILINGUAL TEACHING BAGI GURU MTS HIFAL BANYURIP PEKALONGAN - Inayatul Ulya; Sarlita D. Matra (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2022)
The availability of a bilingual class whose learning process uses two languages ​​of instruction, namely Indonesian and English, is expected to be the answer to problems in an effort to increase the competitiveness of the Indonesian generation to the international world. The application of the Bilingual Class at Mts Hidayatul Athfal (HIFAL) is one of the flagship programs that it has as an effort to improve the quality of students at the school. This is the flagship program of MTs HIFAL, however, there are new challenges for school administrators considering that not all teachers are able to speak English fluently. Therefore, the school really needs Bilingual Teaching training for MTs HIFAL Banyurip teachers, Pekalongan. By holding training through community service activities, it is hoped that the teaching skills of teachers in bilingual languages ​​can be improved. This training also involves native speaker who help participants to practice using English. Bilingual Teaching training activities for MTs Hidayatul HIFAL) teachers provided significant benefits for participants. By participating in these activities, participants gain material and experience that can be applied to the Bilingual class. In the microteaching session, participants have implemented the preparation of bilingual learning tools, the use of Teachers Talk in bilingual learning, the use of ICT in bilingual learning, and the use of cooperative learning methods in bilingual learning. By participating in this training, most of the participants (teachers) seemed more confident in using English for daily communication, especially for teaching. Their speaking and teaching skills using the bilingual language are improved. Keywords: Bilingual; Training; Teaching